Avoiding damage to transvenous leads—A comparison of electrocautery techniques and two insulated electrocautery blades. - Wasserlauf, Jeremiah; Esheim, Taiki; Jarett, Natasha M.; Chan, Eric K.Y.; Schaller, Robert D.; Garcia, Fermin C.; Knight, Bradley P. (Pacing & Clinical Electrophysiology, 2018)
Background: Electrocautery (cautery) can damage transvenous cardiac device leads. The purpose of this study was to compare lead damage from an insulated cautery blade when used with several different techniques that included coagulation (COAG) versus cutting (CUT) mode, perpendicular active edge (active) versus parallel flat blade (flat) orientation (phase 1), and using one commercially available blade (PhotonBlade) versus another (PlasmaBlade) (phase 2). Methods: In phase 1, lesions were delivered using combinations of: (1) COAG and CUT; (2) active and flat orientation; and (3) polyurethane, silicone, and copolymer insulation. In phase 2, lesions were delivered using combinations of: (1) PlasmaBlade and PhotonBlade, (2) four power output levels, and (3) eight different lead models. Lead damage was scored on an ordinal scale of 0 to 4. Results: Phase 1: more leads were damaged using COAG than CUT (48% vs 2%, P < 0.0001). When using COAG, 74% of lesions using active orientation had damage versus 22% of lesions using flat orientation (P  =  0.0002). COAG lesions to copolymer (61%) and polyurethane (68%) leads had greater damage than silicone (17%) (P  =  0.006 and P  =  0.003, respectively). Phase 2: 75% of treatments using PlasmaBlade had damage versus 40% of treatments with PhotonBlade (P < 0.0001). Higher power resulted in more damage. At the commonly used setting of CUT 20 W, damage occurred in 39% of treatments using PlasmaBlade versus 13% using PhotonBlade (P  =  0.0006). Conclusions: COAG resulted in more damage than CUT; this effect was greatest with the active edge, and with polyurethane or copolymer insulation. PhotonBlade was associated with less damage to leads than PlasmaBlade.